Investigation and analysis of finger breakages in commercial crystalline silicon photovoltaic modules under standard thermal cycling test. (July 2019) - Roy, Subinoy; Kumar, Sagarika; Gupta, Rajesh
Abstract: The front grid fingers play a major role in the conduction of current in crystalline silicon photovoltaic (PV) modules. These fingers generally break with time during the field exposure which affects the modules mechanical and electrical integrity and causes reduction in its performance. In this paper, a systematic methodology has been presented for investigation of the nature and evolution of finger breakages observed in crystalline silicon PV technology modules under standard thermal cycling tests as specified under IEC 61215 standard. Illuminated current-voltage (I-V) analysis and electroluminescence (EL) imaging techniques have been exploited in tandem for investigation of the cause, types and progression of the finger breakages. The results obtained from the study identified various faulty solder configurations which are sensitive to thermal fatigue and subsequently cause finger breakages. A generalized method to quantify the finger breakages from EL images has been introduced. The different finger breakage patterns have been classified according to their appearance in the EL images originating from the breakage of the busbar-finger junctions. Distributed diode modelling and simulation have also been performed for the quantification of severity of different finger breakage patterns. In addition, a finger breakage constant has been proposed for comparative assessment of durability of fingers in PV modules under thermal cycling test conditions. The present investigation and analysis of finger breakages can be instrumental in prevention of failures thereby enhancing performance and durability of PV modules. Highlights: Crystalline silicon PV modules subjected to standard thermal cycles. Characterization of finger breakages by EL imaging and illuminated I-V technique. Dislocated ribbon on top of busbar produced most significant finger breakages. Classification of finger breakages and simulation of their impacts. Quantification method for finger breakages, showed saturation at higher cycles.